ALS is a multistep process in South Korean, Japanese, and Australian patients. (14th April 2020) - Vucic, Steve; Higashihara, Mana; Sobue, Gen; Atsuta, Naoki; Doi, Yuriko; Kuwabara, Satoshi; Kim, Seung Hyun; Kim, Inah; Oh, Ki-Wook; Park, Jinseok; Kim, Eun Mi; Talman, Paul; et al.
Abstract : Objective: To establish whether amyotrophic lateral sclerosis (ALS) is a multistep process in South Korean and Japanese populations when compared to Australian cohorts. Methods: We generated incident data by age and sex for Japanese (collected between April 2009 and March 2010) and South Korean patients with ALS (collected between January 2011 and December 2015). Mortality rates were provided for Australian patients with ALS (collected between 2007 and 2016). We regressed the log of age-specific incidence against the log of age with least squares regression for each ALS population. Results: We identified 11, 834 cases of ALS from the 3 populations, including 6, 524 Australian, 2, 264 Japanese, and 3, 049 South Korean ALS cases. We established a linear relation between the log incidence and log age in the 3 populations: Australia r 2 = 0.99, Japan r 2 = 0.99, South Korea r 2 = 0.99. The estimate slopes were similar across the 3 populations, being 5.4 (95% confidence interval [CI], 4.8–5.5) in Japanese, 5.4 (95% CI, 5.2–5.7) in Australian, and 4.4 (95% CI, 4.2–4.8) in South Korean patients. Conclusions: The linear relationship between log age and log incidence is consistent with a multistage model of disease, with slope estimated suggesting that 6 steps were required in Japanese and Australian patients with ALS while 5 steps were needed in South Korean patients. Identification of these steps could identify novel therapeutic strategies.